Compressive properties of 3D printed auxetic structures: experimental and numerical studies. Issue 1 (2nd January 2020) - Alomarah, Amer; Masood, Syed H.; Sbarski, Igor; Faisal, Batool; Gao, Zhanyuan; Ruan, Dong
ABSTRACT: Metamaterials that exhibit negative Poisson's ratio (NPR) are known as auxetics. They laterally expand or contract when they are axially tensioned or compressed. A re–entrant chiral auxetic structure (RCA) is a recently developed structure, which combines the topological features of re–entrant and chiral honeycombs. Comparative study between the RCA structure and popular benchmarks subjected to uniaxial compression has been conducted experimentally and numerically. Specimens have been fabricated from polyamide12 (PA12) using Multi Jet Fusion (MJF). Numerical models have been developed using ABAQUS/Explicit and verified by the experiments. The experimental measurements manifest the high accuracy of the MJF process to produce robust components with precise details. It has been found that the RCA structure outperforms the other types of honeycombs in terms of strength and specific energy absorption when loaded in the Y direction, while only the tetrachiral honeycomb surpasses the RCA structure in terms of specific energy absorption when loaded in the X direction. The auxeticity (NPR) of the RCA structure compressed in the Y direction was larger than that of the other honeycombs. Numerical models have been employed to study the effects of friction and the number of cells on the mechanical response of the RCA structure.